Biology and clinical relevance of EpCAM - Keller, Laura; Werner, Stefan; Pantel, Klaus (Cell Stress, 2019)
Epithelial cell adhesion molecule (EpCAM) is a transmembrane glycoprotein primarily known to mediate homotypic cell contacts in epithelia tissues. Because EpCAM expression is limited to normal and malignant epithelia, it has been used as diagnostic marker for the detection of carcinoma cells in mesenchymal organs such as blood, bone marrow or lymph nodes. In particular, the detection and molecular characterization of EpCAM-positive circulating tumor cells (CTCs) in the blood of carcinoma patients has gained considerable interest over the past ten years. EpCAM is primarily considered as an adhesion molecule, but recent studies have shown diverse biological functions including regulation of cell proliferation and cancer stemness. In this review, we summarize the current knowledge on the biological properties of EpCAM with emphasis on mechanisms involved in cancer progression and discuss the clinical implications of these findings for the clinical use of EpCAM as a diagnostic marker.